Emergence of Fungicide Sensitivity in Leptosphaeria maculans Isolates Collected from the Czech Republic to DMI Fungicides - Olufadekemi Fajemisin; Jana Mazáková; Pavel Ryšánek (Agriculture, 2022)
In the Czech Republic, demethylation inhibitors (DMIs) are used both as fungicides in controlling phoma stem canker and as growth regulators. This heavy use can result in the development of resistant isolates. A total of 45 and 286 Leptosphaeria maculans isolates were tested in vitro, using the mycelial growth and microtiter plate assays, respectively. The objective was to determine the sensitivity of L. maculans isolates collected in the Czech Republic to the fungicides tetraconazole, metconazole, and prochloraz. The mean EC50 values with the mycelial growth plate method were 1.33, 0.78, and 0.40 µg mL−1 for tetraconazole, metconazole, and prochloraz, respectively. The mean EC50 values for the microtiter plate assay were 3.01, 0.44, and 0.19 µg mL−1 for tetraconazole, metconazole, and prochloraz, respectively. All three fungicides also had high variation factors that may be due to inserts in the ERG11 promoter region. In addition, cross sensitivity among the three fungicides was observed. Overall, the high variation factors and the PCR (polymerase chain reaction) results observed in this study could signify the presence of resistant isolates in L. maculans Czech populations, especially in isolates tested for sensitivity to tetraconazole.